Shelf Life Estimation of “So Lite” Fish Nugget - Amalia, Ulfah (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
Fish nugget is a food product with a high degree of risk because it has a degree of acidity greater than 4.5 and more than 0.85 for water activity. Based on this risk, the companies generally put storage adviceinformation on the fish nuggets packaging, as a quality parameter of the product. One method that is simple enough to be applied in the expected shelf life by measuring the rate of decline in the quality parameter is Arrhenius model. The purpose of this analysis was to determined the basis used by a company in the food product shelf-life estimation in this case is a nugget of fish products with trademarks Fish Nugget '’So Lite